Hubungan Tingkat Stres dengan Keteraturan Siklus Menstruasi Pada Remaja Kelas XII di SMK Batik 1 Surakarta - Rosiana, Daisa, dr. Rh Budhi Muljanto, Sp.KJ, dr. Sri Wahyu Basuki, M.Kes (2016)
Background: Menstruation is a natural process of women it is a process of an endometrium wall disintegration that comes out with blood through a vagina. The menstrual cycle normally happened within 21 - 35 days. Stress is one factor that affects the menstrual cycle because it can lead to an emphasis on hormones. In adolescents frequent emotional tension increased thus affecting the performance of hormones and menstrual cycle regularity Objective: To determine the relationship between stress level with the regularity of menstrual cycle in teenagers Batik 1 State Vocational High School class XII Surakarta. Methods: This study was analytic observational and using cross sectional approach and the sample taken from the population that have met the criteria for inclusion are 122 respondents, the sampling technique used is total sampling. Methods of collecting primary data sheet LMMPI, PSS-10, questionnaire menstrual cycle and data analysis with Chi-Square test. Results: The analysis of the data showed p value <0.05 is 0.000 which shows the significant value means there is a relationship between stress level with the regularity of menstrual cycles in teenagers Batik 1 State Vocation High School class XII Surakarta. Conclusion: There is a relationship between stress level with the regularity of menstrual cycles in teenagers Batik 1 State Vocational High School class XII Surakarta.